2001
DOI: 10.1046/j.1460-9592.2001.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of single dose caudal tramadol, tramadol plus bupivacaine and bupivacaine administration for postoperative analgesia in children

Abstract: Tramadol used caudally is as effective as bupivacaine in the management of postoperative pain in children and the addition of tramadol to bupivacaine, when both drugs were administered caudally, did not prolong the duration of action of bupivacaine and is a safe agent in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 14 publications
3
15
0
5
Order By: Relevance
“…Ropivacaine, a new local anesthetic agent, has been reported to have lower toxic effects on the cardiovascular and central nervous systems [12,13]. Although tramadol, a weak opioid synthesized in recent years, has been reported to be effective in caudal blockade in children, studies regarding its use in lumbar epidural blockade are rare [14][15][16][17]. On the other hand, previous studies have also shown that epidural or caudal tramadol can be free from postoperative analgesia-related side effects [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Ropivacaine, a new local anesthetic agent, has been reported to have lower toxic effects on the cardiovascular and central nervous systems [12,13]. Although tramadol, a weak opioid synthesized in recent years, has been reported to be effective in caudal blockade in children, studies regarding its use in lumbar epidural blockade are rare [14][15][16][17]. On the other hand, previous studies have also shown that epidural or caudal tramadol can be free from postoperative analgesia-related side effects [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Many drugs including epinephrine, morphine 11 , clonidine 11 , ketamine 11 , and tramadol 12,13 have been co-administered with caudal bupivacaine to maximize and extend the duration of analgesia. Morphine extends the duration of analgesia but frequent association of delayed respiratory depression, itching, vomiting, and postoperative retention of urine has limited its use 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Morphine extends the duration of analgesia but frequent association of delayed respiratory depression, itching, vomiting, and postoperative retention of urine has limited its use 14 . Behavioral side effects are reported with use of ketamine and increased incidence of vomiting was observed with use of tramadol 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, owing to its nonopioid receptor‐mediated actions, tramadol may produce less respiratory depressions (25). However, common side effects including nausea and vomiting may be seen following tramadol administration (36). Nonetheless, Prakash and colleagues did not observe any adverse effects in caudal administration of tramadol (16).…”
Section: Discussionmentioning
confidence: 99%